INTERDISCIPLINARY APPROACH IN TREATMENT OF PATIENTS WITH DENTAL ANOMALIES - l.V. Smahlyuk; N.V. Kulish; O. M. Nesterenko (Український стоматологічний альманах)
The article presents data on the treatment of patients with TMJ and concomitant deformities. The most important connection between the dental system and the musculoskeletal system is the temporomandibular joint, which in the presence of dental anomalies and in the period of temporary occlusion undergoes increased loads, which leads to its dysfunction. The concept of the interaction of posture and occlusion was first put forward in the early 20th century, which noted that children with glossoptosis have X-shaped legs, crooked posture and typical signs of distal occlusion. It has been theorized that occlusal disorders can alter posture in the frontal and sagittal planes and ultimately alter body weight distribution. Postural curvature causes a violation of the position of the head of the temporomandibular joint, which in turn leads to pain and joint dysfunction. Any postural disorders lead to compensatory changes throughout the body, not excluding the maxillofacial area. This is especially true for the formation of mesial occlusion (III class according to Angle). Mesial occlusion in the structure of dental anomalies is determined in 12% of cases, but the severity of the anomaly and aesthetic disorders that occur often force orthodontists to use a combination.